On site challenges for the construction of 16-storey condominium: as observed by a young civil engineering technologist - Ganageswaran, S.; Srinivasan, M.; Chan, C. M. (Penerbit UTHM, 2020)
The difference between an engineer and an engineering technologist is that, an engineer would mainly focus and produce structural designs based on engineering calculations, while the job of an engineering technologist is to execute the design in the real working environment by adopting flexible and critical technical ideas on-site. The challenges can be divided into two categories, namely design challenges faced by an engineer and the construction challenges faced by an engineering technologist. Thus, the job scope of an engineering technologist is relatively wider when compared to that of an engineer, as the engineering technologist would be dealing with the consultant, contractors and suppliers on site, while handling the in situ construction challenges. This requires basic understanding of engineering principles and technology, critical thinking and problem-solving skills, modern tools competency in software applications, designs and construction calculations, as well as communication and leadership skills all rolled into one. I have recorded my experience as a junior civil engineering technologist engaged in the construction works of a 16-storey condominium at Langkawi, Kedah. Included in the descriptions are in situ technical problems encountered, potentially unsafe working conditions, foundations, scheduling and housekeeping on site, among others. I hope that the information shared in this entry would make a good introduction and induction for juniors entering the work site, where my personal undertakings could serve as a guide and reminder for them.